Design, manufacturing and testing of a landing gear wheel mechanism for a quadcopter - Lee, Nicholas (2017)
Quadcopters have been rapidly gaining in popularity and as a result have seen an increase in their development over the past few years, with individuals experimenting on various methods and means to expand on their capabilities. Hybrid designs are one such area which have often piqued the interest of developers, with the possibilities that can be granted to an existing model. Having multiple capabilities on a single platform allows the user to push the boundaries of what the craft can do. This final year project explored the possibilities of adding ground capabilities to the conventional quadcopter using a landing gear wheel mechanism. A detailed design was developed using computer aided drawings and simulations were run on Abaqus to test the ability of design to withstand the weight of the quadcopter and forces during landing. Subsequently, the compact landing gear system was manufactured and tested thoroughly in a controlled environment. The final design selected was able meet the requirements, and was successful in the integration of the landing gear and the quadcopter. This report highlights the main principles and concepts used during the design process, and the methodology used in the testing and prototyping phase. The report also highlights the limitations of the design and provides several improvements and recommendations including concepts for a new design. The new design could serve as a platform for future works which can expand on the concepts used in this project to further push the boundaries of hybrid designs.